Jesuits and Conversos as a “Tragic Couple”: Introductory Remarks - Sṭuts'insḳi, Dov (Journal of Jesuit studies, 2021)
Abstract This article introduces the phenomenon of Jesuit-converso interactions, mostly in the early modern Iberian world. It summarizes the shifting attitudes of the Society of Jesus vis-à-vis New Christians of Jewish origin as actual or potential Jesuits and maps the multifaceted and variegated interplay between Jesuit priests and converso laymen, understood as a “tragic couple” relationship. This brief survey emphasizes the historiographical contribution of the last generations of Jesuit scholars, and of the five articles included in this special issue of the Journal of Jesuit Studies , to disclose a more overt “historical memory” of the Society of Jesus.